Dominant KCNA2 mutation causes episodic ataxia and pharmacoresponsive epilepsy. (8th November 2016) - Corbett, Mark A.; Bellows, Susannah T.; Li, Melody; Carroll, Renée; Micallef, Silvana; Carvill, Gemma L.; Myers, Candace T.; Howell, Katherine B.; Maljevic, Snezana; Lerche, Holger; Gazina, Elena V.; Mefford, Heather C.; et al.
Abstract : Objective: To identify the genetic basis of a family segregating episodic ataxia, infantile seizures, and heterogeneous epilepsies and to study the phenotypic spectrum of KCNA2 mutations. Methods: A family with 7 affected individuals over 3 generations underwent detailed phenotyping. Whole genome sequencing was performed on a mildly affected grandmother and her grandson with epileptic encephalopathy (EE). Segregating variants were filtered and prioritized based on functional annotations. The effects of the mutation on channel function were analyzed in vitro by voltage clamp assay and in silico by molecular modeling. KCNA2 was sequenced in 35 probands with heterogeneous phenotypes. Results: The 7 family members had episodic ataxia (5), self-limited infantile seizures (5), evolving to genetic generalized epilepsy (4), focal seizures (2), and EE (1). They had a segregating novel mutation in the shaker type voltage-gated potassium channel KCNA2 (CCDS_827.1: c.765_773del; p.255_257del). A rare missense SCN2A (rs200884216) variant was also found in 2 affected siblings and their unaffected mother. The p.255_257del mutation caused dominant negative loss of channel function. Molecular modeling predicted repositioning of critical arginine residues in the voltage-sensing domain. KCNA2 sequencing revealed 1 de novo mutation (CCDS_827.1: c.890G>A; p.Arg297Gln) in a girl with EE, ataxia, and tremor. Conclusions: A KCNA2 mutation caused dominantly inherited episodic ataxia, mild infantile-onset seizures, and later generalized and focal epilepsies in the setting of normal intellect. This observation expands the KCNA2 phenotypic spectrum from EE often associated with chronic ataxia, reflecting the marked variation in severity observed in many ion channel disorders.